Clinical prevalence of stroke in a tertiary care hospital in Southern India - Kannan, Vinoth; Justin, C.; Prashanth, P. R. Sai; Alexander, Neenu (International Journal of Research in Medical Sciences, 2021)
Background: Stroke is the second most deadly disease in the world next only to ischemic heart disease. The incidence of stroke continues to rise particularly among young individuals. Given the paucity of data and lack of reliable reporting mechanisms, understanding the epidemiology of stroke in India is challenging. This study aims to review the prevalence of stroke in a tertiary care hospital in southern India. Methods: The study includes all the Stroke patients admitted in Government Rajaji Hospital and Madurai Medical College, Madurai during the period of 01 January 2018 to 31 December 2018. Results: A total of 1168 patients were taken into study, there were 779 males and 389 females. There were a total of 848 ischaemic stroke patients (72.60%), when compared to 320 haemorrhagic stroke patients 27.39%. Anterior circulation stroke prevalence was higher (88.27%) when compared to posterior circulation stroke. A total 498 patients (42.63%) belonged to the age group of 40 to 60 years. Conclusions: There is inadequate data regarding the prevalence of stroke in India and decade old data indicates that there is an increasing prevalence. Hence the study reviewed the current prevalence of stroke in a tertiary care centre in southern Tamil Nadu.